2023
DOI: 10.3390/ijerph20075406
|View full text |Cite
|
Sign up to set email alerts
|

Child-Owned Poultry Intervention Effects on Hemoglobin, Anemia, Concurrent Anemia and Stunting, and Morbidity Status of Young Children in Southern Ethiopia: A Cluster Randomized Controlled Community Trial

Abstract: Cereal-based diets contribute to anemia in Ethiopian children. Eggs have nutrients to boost hemoglobin levels as well as counter concurrent anemia and stunting (CAS) and morbidity status. A community trial, targeting 6–18 months old children, was conducted in Halaba. Two clusters were randomly selected and allocated to intervention (N = 122) and control (N = 121) arms. Intervention group (IG) children received egg-laying hens with caging in a cultural ceremony declaring child ownership of the chickens. Parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…Consistent with our findings, other studies (Custodio et al, 2008 ; Jankowska et al, 2012 ; Omer & Hailu, 2023 ; Osei et al, 2017 ) have also found that poultry provides a protective advantage against anemia in children. Perhaps, not all studies have showed beneficial effects, as there are also some observational and experimental studies showing a reverse association or effect (Olney et al, 2009 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our findings, other studies (Custodio et al, 2008 ; Jankowska et al, 2012 ; Omer & Hailu, 2023 ; Osei et al, 2017 ) have also found that poultry provides a protective advantage against anemia in children. Perhaps, not all studies have showed beneficial effects, as there are also some observational and experimental studies showing a reverse association or effect (Olney et al, 2009 ).…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, theoretical studies have also shown that livestock keeping may lead to infection (Cash‐Goldwasser et al, 2018 ; Raghunathan et al, 2005 ; Zerfu et al, 2022 ), and that infection and inflammation contribute to anemia (Hasyim et al, 2018 ; LaBeaud et al, 2015 ; Lambrecht et al, 2022 ). However, there is insufficient evidence to conclude whether livestock production improves, or remains unrelated to childhood anemia in LMIC settings (Lambrecht et al, 2019 ), including Ethiopia (Abdurahman & Id, 2021 ; Omer & Hailu, 2023 ; Passarelli et al, 2020 ). Furthermore, existing evidence on the relationship between livestock ownership and its health consequences is mainly based on observational studies that are short of causal‐effect association.…”
Section: Introductionmentioning
confidence: 99%